Carotid atherosclerosis in postmenopausal patients with undifferentiated connective tissue dysplasia - M. A. Shambatov; N. V. Izmozherova; A. A. Popov; I. F. Grishina; A. A. Vikhareva; G. B. Kolotova (Лечащий Врач)
Objective. To evaluate the relationship between undifferentiated connective tissue dysplasia and atherosclerosis of the brachiocephalic arteries (BCA) in postmenopausal women.Materials and methods. A cross-sectional study enrolled 120 women, aged 68 (65 ± 70) years, the duration of menopause: 18 (16 ± 21) years. Ultrasound duplex scanning of the of the brachiocephalic zone arteries extracranial parts has been performed. The normal thickness of the intima-media complex (TIMT) was considered to be < 0.9 mm, an increase in TIMT of more than 1.3 mm was interpreted as the presence of an atherosclerotic plaque (AP). Total cholesterol, high density lipoprotein cholesterol, low density lipoproteins cholesterol, serum triglyceride levels were assessed by the enzymatic colorimetric method. UCTD was verified according to the clinical guidelines the Russian Scientific Medical Society of Therapists. The first group consisted of 27 (22.5%) people with verified undifferentiated connective tissue dysplasia. The second group included 93 (77.5%) women without undifferentiated connective tissue dysplasia. The measure of data averaging is the median (Me), the measure of dispersion is the interquartile range (Q1 ± Q3). Mann – Whitney, χ2 – Pearson tests were used. Differences, associations and correlations were considered significant at p < 0.05.Results. Thickening of IMT was detected in 18 (67%) cases in Group 1 and in 63 (65%) cases in Group 2, the differences were not significant. Atherosclerotic plaques were found in 17 (63%) patients of the Group 1 and 62 (67%) patients of the Group2. Only 23 (19%) study participants has adequate serum vitamin D levels, in 97 (81%) cases, a decrease in the serum level of 25-hydroxyvitamin D ≤ 30 ng/ml was detected. No direct relationship was found between the serum vitamin D level and the brachiocephalic arteries intima-media complex thickness. Vitamin D deficiency was associated with higher LDL cholesterol (p = 0.03) and lower HDL cholesterol (p = 0.03) levels. Patients with UCTD had more frequent pathological tortuosity of the vertebral artery: 8 (30%) in Group 1 versus 9 (9%) in Group 2 (χ2 = 5.77, df = 1, p = 0.017). When assessing the linear parameters of blood flow in the brachiocephalic arteries in local samples, significant differences were found only in the right vertebral artery diastolic velocity values. However, in patients with UCTD, which is associated with the use of resistive properties of blood vessels.Conclusion. In this study, more than half of postmenopausal patients with arterial hypertension atherosclerotic lesion of brachiocephalic arteries has been revealed. In the presence of UCTD criteria, pathological tortuosity of the vertebral arteries was more often detected. A decrease in diastolic velocity against the background of low values of the pulsation index of the vertebral artery in patients with UCTD may be a consequence of the participation of vertebral arteries in extracerebral and intracerebral circulation aimed at preserving regional blood flow of the brain against a background of a more significant decrease in the elastic properties of the arteries.